Синтез олігоуретанів на основі ріпакової та лляної олій - Віленський, В.О.; Керча, Ю.Ю.; Гончаренко, Л.А.; Глієва, Г.Є. (Видавничий дім "Академперіодика" НАН України, 2008)
The possibility of utilization of oxidized rapeseed and linseed oils as reactive compounds for oligourethanes is first shown. The depth of oxidation of vegetable oils and the properties of oligomeric products are determined by the chemical constitution of oils and the choice of oxidizers.